International scientific conference dedicated to the anniversary of 110th birthday of Kvasnikov B.V - Editorial Article (Овощи России)
On the 25th of February 2009 the international scientific conference was held at All-Russian Research Institute of Vegetable Growing, RAAS. This meeting was to mark the 110th birthday of Kvasnikov B.V. meritorious and outstanding plant breeding specialist, the honoured scientist in agriculture science.